APLIKASI DETEKSI KEMIRIPAN TUGAS PAPER - Anthony Anggrawan; Azhari Azhari (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2016)
Information searching based on users’ query, which is hopefully able to fnd the documents based on users’ need, is known as Information Retrieval. This research uses Vector Space Model method in determining the similarity percentage of each student’s assignment. This research uses PHP programming and MySQL database. The fnding is represented by ranking the similarity of document with query, with mean average precision value of 0,874. It shows how accurate the application with the examination done by the experts, which is gained from the evaluation with 5 queries that is compared to 25 samples of documents. If the number of counted assignments has higher similarity, thus the process of similarity counting needs more time, it depends on the assignment’s number which is submitted.